tire
The tire design addresses crack resistance and durability issues by optimizing rubber composition and incorporating micro-protuberances, resulting in improved sidewall performance and extended tire lifespan.
Patent Information
- Application Number
- JP2023102742
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-22
- Publication Date
- 2025-01-09
AI Technical Summary
Tires face challenges in extending lifespan and improving crack resistance, particularly in the sidewalls, which are crucial for reducing environmental impact and enhancing fuel efficiency.
A tire design incorporating specific rubber composition properties, including loss tangent, complex modulus of elasticity, bead apex height, and micro-protuberances on the sidewalls, along with the use of silica and recovered carbon black, to enhance crack resistance and flexibility.
The design improves crack resistance by reducing heat generation and stress concentration, leading to enhanced durability and flexibility, thereby extending the tire's lifespan and maintaining high load capacity.
Smart Images

Figure 2025002514000006 
Figure 2025002514000007 
Figure 2025002514000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a tire. [Background technology]
[0002] As the demand for fuel efficiency of tires increases, fuel efficiency is being considered not only in the tread portion of tires but also in other components such as sidewalls in order to improve the fuel efficiency of tires. For example, Patent Document 1 describes that fuel efficiency can be improved by using a rubber composition containing a specific resin in the sidewall of a tire. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-14506 Summary of the Invention [Problem to be solved by the invention]
[0004] On the other hand, from the viewpoint of reducing the environmental impact, there is also a demand for further extending the life of tires, and there is room for improvement in terms of improving the crack resistance of the sidewall and further extending the life of the tires.
[0005] An object of the present invention is to improve the crack resistance of the sidewall. [Means for solving the problem]
[0006] The present invention relates to the following tire. A tire having a pair of sidewalls and a pair of bead apexes, A tire in which 70°C tan δ, 70°C E*, H, G and WL satisfy the following relationship, where the loss tangent (tan δ) at 70°C of the rubber composition constituting the sidewall is 70°C tan δ, the complex modulus of elasticity (MPa) of the rubber composition at 70°C is 70°C E*, the height (mm) of the bead apex is H, the tire weight (kg) of the tire is G, and the maximum load capacity (kg) is WL. (1) 0.006×H-70℃ tan δ>0.320 (2) 70℃E*<10.0 (3) G / WL<0.0180 Effect of the Invention
[0007] According to the present invention, the crack resistance of the sidewall can be improved. [Brief description of the drawings]
[0008] [Figure 1] 1 is a diagram showing a tire section width Wt, a tire section height Ht, and a tire outer diameter Dt in a cross section of a tire taken along a plane including the tire rotation axis, and further showing a bead apex height H and a sidewall thickness T. [Diagram 2] 1 is a diagram showing a tire cross-sectional width Wt, a tire cross-sectional height Ht, and a tire outer diameter Dt in a cross section of a tire taken along a plane including the tire rotation axis, and further showing a bead apex height H when a bead reinforcing layer is provided. [Diagram 3] 1 is a schematic diagram of an outer surface of a sidewall having a plurality of columnar micro-ridges formed thereon. [Figure 4] 1 is a schematic diagram of the outer surface of a sidewall on which a plurality of tiny pyramidal frustum-shaped protuberances are formed. [Diagram 5] XX cross-sectional view of FIG. 4. [Figure 6] 1 is a schematic diagram of an outer surface of a sidewall having a plurality of rib-like micro-ridges formed thereon. [Figure 7] 7 is a cross-sectional view of FIG. 6 taken along the line YY. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention relates to the following tire. A tire having a pair of sidewalls and a pair of bead apexes, A tire in which 70°C tan δ, 70°C E*, H, G and WL satisfy the following relationship, where the loss tangent (tan δ) at 70°C of the rubber composition constituting the sidewall is 70°C tan δ, the complex modulus of elasticity (MPa) of the rubber composition at 70°C is 70°C E*, the height (mm) of the bead apex is H, the tire weight (kg) of the tire is G, and the maximum load capacity (kg) is WL. (1) 0.006×H-70℃ tan δ>0.320 (2) 70℃E*<10.0 (3) G / WL<0.0180
[0010] Although not intending to be bound by theory, the following mechanism is considered to be the mechanism by which the crack resistance performance of the sidewall can be improved in the present invention. That is, since the sidewall deforms when the tire rolls, the accumulation of deformation due to running makes it easy for cracks to occur. In contrast, in the tire of the present invention, (A) as shown in the above formula (1), the loss tangent tan δ of the sidewall is adjusted according to the height of the bead apex. It is considered that when the tan δ of the sidewall is high, the rubber is easily broken due to heat generated during rolling, and cracks are easily generated, but it is considered that by having a sufficient height of the bead apex, deformation can be suppressed and heat generation can also be reduced. On the other hand, when the height of the bead apex is low, the loss tangent tan δ of the sidewall rubber becomes small, which is considered to suppress heat generation and contribute to suppression of cracks. In addition, (B) as shown in the above formula (2), since the complex elastic modulus of the sidewall rubber is a predetermined value or less and is soft, it can flexibly deform in response to strain generated on the surface, which is considered to contribute to suppression of cracks. Furthermore, (C) as shown in the above formula (3), the maximum load capacity relative to the tire weight is increased. The maximum load capacity of a tire is proportional to the tire's volume, and it is believed that increasing the maximum load capacity relative to the tire weight can reduce the tire's overall thickness and improve the heat dissipation effect. Furthermore, these (A) to (C) work together to suppress heat generation and heat accumulation in the sidewall, while ensuring flexibility on the sidewall rubber surface and maintaining high fracture resistance, which is believed to improve crack resistance.
[0011] When the thickness of the sidewall at the maximum width position of the tire is T (mm), it is preferable that 70° C. E* and T satisfy the following relationship. (4) 70℃E*×T<31.5
[0012] The lower the 70°C E*, the more flexible the rubber is, allowing it to deform flexibly during deformation, making it easier to prevent cracks from occurring. Furthermore, by making the sidewall thinner, the volume of the rubber is reduced, reducing heat generation and suppressing the temperature rise of the sidewall, making it easier to prevent cracks from occurring. Therefore, by satisfying the relationship of formula (4), the flexibility during deformation and the reduction in heat generation are interrelated, which is thought to improve the crack resistance of the sidewall.
[0013] The rubber composition preferably contains silica.
[0014] It is believed that by compounding a small amount of silica, the rubber is adequately reinforced, making it easier for the silica surfaces to slide against each other, improving the elongation at break (EB). It is also believed that the improved EB suppresses the generation of cracks during large deformation, improving the crack resistance of the sidewall.
[0015] The rubber composition contains carbon black, and the carbon black preferably contains recovered carbon black (rCB).
[0016] Because the surface of the rCB is burned, the bonds with the surrounding rubber molecules tend to be slightly weaker. This makes it easier for the surrounding rubber molecular chains to release force when the tire is deformed, which is thought to improve the crack resistance of the sidewall.
[0017] The rubber composition contains silica and carbon black, and when the content (parts by mass) of the silica relative to 100 parts by mass of the rubber component is S and the content (parts by mass) of the carbon black is C, it is preferable that S and C satisfy the following relationship. (5) S / C>0.50
[0018] By using silica in an amount that is more than half the amount of carbon black, it is believed that the effect of improving the breaking elongation due to silica can be obtained, while the rubber composition can be more easily reinforced and the crack resistance can be more easily improved.
[0019] The rubber composition contains silica and carbon black, the carbon black contains recovered carbon black, and when the content (parts by mass) of the silica relative to 100 parts by mass of the rubber component is S and the content (parts by mass) of the recovered carbon black is rC, it is preferable that S and rC satisfy the following relationship: (6) S / rC>1.00
[0020] It is believed that by making the amount of silica greater than the amount of recovered carbon black, the effect of improving breaking elongation due to silica and the effect of dispersing force due to rCB can be more easily obtained.
[0021] At least one of the pair of side walls preferably has a micro-ridge forming portion having a plurality of micro-ridges formed on an outer surface thereof.
[0022] The presence of the micro-ridges makes it possible to suppress stress concentration on the outer surface of the sidewall, which is believed to contribute to improving the crack resistance of the sidewall.
[0023] The shape of the minute protuberances is preferably columnar, frustum or rib-like.
[0024] By providing the micro-ridges with these predetermined shapes, stress concentration on the outer surface of the sidewall can be suppressed, which is believed to contribute to improving the crack resistance of the sidewall.
[0025] The micro-ridges have a height of 0.03 mm or more and 0.50 mm or less, and 20 or more are formed at intervals of 0.50 mm or less in at least one direction. The micro-ridge formation portion is 2 It is preferable that the area is equal to or larger than this.
[0026] By having the size of the micro-protuberances fall within these prescribed ranges, stress concentration on the outer surface of the sidewall can be suppressed, which is believed to contribute to improving the crack resistance of the sidewall.
[0027] The maximum width of the minute protuberances is preferably 0.03 mm or more and 5.0 mm or less.
[0028] By having the maximum width of the micro-protuberances fall within a prescribed range, stress concentration on the outer surface of the sidewall can be suppressed, which is believed to contribute to improving the crack resistance of the sidewall.
[0029] It is preferable that the height of the minute protuberances gradually increases from the maximum tire width position toward the outside in the tire radial direction, and gradually increases from the maximum tire width position toward the inside in the tire radial direction.
[0030] Relatively large distortion occurs near the sidewall at the widest point of the tire, but by making the height of the micro-bumps lower on the side closer to the widest point of the tire, it is believed that this reduces the unevenness in the rubber volume in the circumferential direction of the tire at the point where large distortion occurs, avoids stress concentration near the micro-bumps, and contributes to improving the crack resistance of the sidewall.
[0031] <Definition> "Normal condition" refers to a condition where the tire is mounted on a normal rim, inflated to normal internal pressure, and unloaded. "Dimensions, etc. of each part of the tire" are values specified in the normal condition, unless otherwise specified.
[0032] "Genuine rim" refers to a rim that is specified for each tire by the standard system that includes the standard on which the tire is based, such as the standard rim for the applicable size listed in the "JATMA YEAR BOOK" for JATMA (Japan Automobile Tire Manufacturers Association), the "Measuring Rim" listed in the "STANDARDS MANUAL" for ETRTO (The European Tyre and Rim Technical Organisation), and the "Design Rim" listed in the "YEAR BOOK" for TRA (The Tire and Rim Association, Inc.), referring to JATMA, ETRTO, and TRA in that order, and following the standard if there is an applicable size at the time of reference. In the case of a tire not specified in the standard, it refers to a rim that can be assembled to a rim and can hold internal pressure, that is, a rim that does not leak air from between the rim and tire, with the smallest rim diameter and the next narrowest rim width.
[0033] "Regular internal pressure" refers to the air pressure set for each tire by each standard in the standard system including the standard on which the tire is based. For JATMA, it is the "maximum air pressure", for ETRTO, it is the "INFLATION PRESSURE", and for TRA, it is the maximum value listed in the table "TIRE LOAD LIMITS AT VARIOUS COLD INFLATION PRESSURES". As with regular rims, refer to JATMA, ETRTO, and TRA in that order, and follow the standard if there is an applicable size at the time of reference. In the case of a tire not specified in the standard, it refers to the regular internal pressure (250KPa or more) of another tire size (specified in the standard) that is specified with the regular rim as the standard rim. Note that if multiple regular internal pressures of 250KPa or more are specified, it refers to the smallest value among them.
[0034] "Bead apex height (H) (mm)" refers to the distance from the lower end of the bead apex to the upper end of the bead apex in a tire cross section including the tire rotation axis. Here, the lower end of the bead apex refers to the upper end of the bead core, and the upper end of the bead apex refers to the outermost point of the bead apex in the tire radial direction. However, if a bead reinforcing layer is present, the upper end of the bead apex refers to the outermost point of the bead reinforcing layer in the tire radial direction. The bead reinforcing layer is a layer that reinforces the bead portion provided on the outer side in the tire width direction of the turnup portion of the carcass that turns around the bead portion from the inner side to the outer side in the tire width direction.
[0035] "Tire weight (G) (kg)" is the weight of the tire itself, excluding the weight of the rim. In addition, if sound-deadening material, sealant, sensors, etc. are attached to the tire cavity, G is the value including the weight of these items.
[0036] "Maximum load capacity (WL) (kg)" is a value calculated by the following formulas (A) and (B) when the tire section width, tire section height, and tire outer diameter measured under normal conditions are Wt (mm), Ht (mm), and Dt (mm), respectively. V is the virtual volume of the space occupied by the tire. The tire section width Wt is the maximum width between the outer surfaces of the sidewalls under normal conditions, excluding patterns or letters, if any, on the tire side. The tire section height Ht is the distance from the bottom surface of the bead to the outermost surface of the tread, and is half the difference between the tire outer diameter Dt and the rim diameter R (mm). V = {(Dt / 2) 2 -(Dt / 2-Ht) 2}×π×Wt (A) WL=0.000011×V+100 (B)
[0037] "Sidewall thickness (T) (mm)" refers to the thickness (mm) of the rubber constituting the sidewall, measured on the normal line L to the tire surface at the tire maximum width position PW of the sidewall. "Tire maximum width position PW" refers to the position on the sidewall surface where the tire cross-sectional width Wt is measured.
[0038] The term "micro-ridge" refers to a convex protuberance having a height of 0.03 mm to 5.0 mm formed on the outer surface of the sidewall. The maximum width of the micro-ridge is preferably 0.03 mm to 5.0 mm.
[0039] The "microridge formation portion" refers to the portion on the outer surface of the sidewall where the microridges are formed.
[0040] "Recovered carbon black" refers to carbon black obtained from the pyrolysis process of products such as used tires that contain carbon black, and which, when subjected to oxidative combustion by heating in air in a thermogravimetric measurement method conforming to JIS K 6226-2:2003, has a mass ratio of ash (ash content), which is a component that does not burn, of 13 mass% or more. In other words, the mass (carbon content) of the part lost due to the oxidative combustion is 87 mass% or less. Recovered carbon black is sometimes expressed as rCB.
[0041] The "plasticizer content" includes the amount of plasticizer in the rubber component extended by the plasticizer. Similarly, the "oil content" includes the amount of oil contained in the oil-extended rubber.
[0042] <Measurement method> "Styrene content" is 1 It is calculated by H-NMR measurement.
[0043] The "vinyl bond content (1,2-bonded butadiene unit content)" is measured by infrared absorption spectroscopy.
[0044] The "cis content (amount of cis-1,4-bonded butadiene units)" is measured by infrared absorption spectroscopy.
[0045] The "weight average molecular weight (Mw)" can be determined by converting the measured value obtained by gel permeation chromatography (GPC) (GPC-8000 series manufactured by Tosoh Corporation, detector: differential refractometer, column: TSKGEL SUPERMALTPORE HZ-M manufactured by Tosoh Corporation) into a standard polystyrene equivalent.
[0046] "Carbon black N 2 "SA" is the value determined by JIS K 6217-2:2017.
[0047] "Silica N 2 "SA" is a value measured by the BET method in accordance with ASTM D3037-93.
[0048] The "average primary particle size" is calculated by photographing particles with a transmission or scanning electron microscope and taking the arithmetic average of the particle sizes of 400 particles. If the particle shape is nearly circular, the diameter of the circle is used as the particle size, if it is needle-like or rod-like, the short diameter is used as the particle size, and in other cases, the equivalent circle diameter is calculated from the electron microscope image. The equivalent circle diameter is calculated as "4 x (particle area) / positive square root of π". This applies to silica, carbon black, etc.
[0049] "Softening point of resin, etc." means the temperature at which the ball drops when the softening point as specified in JIS K 6220-1:2015 is measured using a ring and ball softening point tester, unless otherwise specified. Softening points measured by other methods are noted accordingly.
[0050] "70℃ tan δ" is measured using a GABO Iplexer series under the following conditions: temperature 70℃, initial strain 10%, dynamic strain ±1%, frequency 10Hz, and elongation mode. When taking samples from tires, take samples of length 20mm x width 4mm x thickness 1mm from inside the rubber layer of the sidewall of each test tire, with the tangential direction in the tire circumferential direction as the long side and the tire width direction as the thickness.
[0051] "70℃E*" is the complex modulus (MPa) measured using a GABO Iplexer series under the conditions of temperature 70℃, initial strain 10%, dynamic strain ±1%, frequency 10Hz, and elongation mode. When taking samples from tires, the same procedure is used as for 70℃ tan δ.
[0052] <Tires> The tire of the present invention will be described below with reference to the drawings as appropriate. However, the drawings are merely examples for the purpose of explanation.
[0053] The tire of the present invention is a tire in which the 70°C tan δ of the rubber composition constituting the sidewall, the 70°C E* of the rubber composition, the bead apex height (mm) H, the tire weight (kg) G, and the maximum load capacity of the tire (kg) WL satisfy the predetermined relationships represented by the above formulas (1), (2), and (3).
[0054] FIG. 1 is a cross-sectional view of a tire having a pair of sidewalls and a pair of bead apex, taken along a plane passing through the tire rotation axis. In FIG. 1, the height of the bead apex (Ba) is indicated by H, which is the distance from the upper end of the bead core (Bc) as the lower end of the bead apex (Ba) to the outermost point in the tire radial direction of the bead apex as the upper end of the bead apex (Ba). FIG. 2 shows a case where the bead portion has a bead reinforcing layer (Br). The bead reinforcing layer (Br) is a layer that reinforces the bead portion and is provided on the outer side in the tire width direction of the turnup portion of the carcass (Cc) that turns around the bead portion from the inner side to the outer side in the tire width direction. In this case, the lower end of the bead apex is the upper end of the bead core (Bc), and the upper end of the bead apex is the outermost point in the tire radial direction of the bead reinforcing layer. 1 and 2 show the tire section width Wt, tire section height Ht, and tire outer diameter Dt (mm) required for calculating the maximum load capacity (WL) of the tire.
[0055] (Formula (1)) The relationship satisfied by formula (1) is as follows. (1) 0.006×H-70℃ tan δ>0.320
[0056] The value of the right side of formula (1) is preferably 0.323, more preferably 0.328, even more preferably 0.329, even more preferably 0.333, and even more preferably 0.339. There is no particular upper limit to the value of the left side of formula (1) from the viewpoint of the effects of the present invention, but it is, for example, 0.600.
[0057] H varies depending on the tire size, but is usually 50 mm or more, preferably 55 mm or more, and more preferably 60 mm or more. In addition, H is not particularly limited from the viewpoint of the effects of the present invention, but is, for example, 110 mm.
[0058] The 70°C tan δ is preferably less than 0.120, more preferably less than 0.110, even more preferably less than 0.100, and even more preferably 0.090 or less. There is no particular restriction on the lower limit of the 70°C tan δ from the viewpoint of the effects of the invention, but for example, it is preferably 0.020 or more, more preferably 0.030 or more, and even more preferably 0.050 or more.
[0059] The 70°C tan δ of the rubber composition can be adjusted appropriately by the type and amount of the components constituting the rubber composition described below. For example, there is a tendency that the 70°C tan δ can be increased by increasing the amount of the filler, decreasing the particle size of the filler, decreasing the amount of the vulcanizing agent and the vulcanization accelerator, etc. Therefore, there is a tendency that the 70°C tan δ can be decreased by the reverse operation.
[0060] (Formula (2)) The relationship satisfied by equation (2) is as follows. (2) 70℃E*<10.0
[0061] The value of the right side of formula (2) is preferably 9.0, more preferably 8.0, even more preferably 7.0, even more preferably 6.0, even more preferably 5.5, even more preferably 4.5, even more preferably 4.0, even more preferably 3.8, even more preferably 3.5, even more preferably 3.0. There is no particular lower limit for the value of the left side of formula (2) from the viewpoint of the effects of the present invention, but it is, for example, 2.0.
[0062] The 70°C E* of the rubber composition can be adjusted appropriately by adjusting the types and amounts of the components constituting the rubber composition described below. For example, there is a tendency that the 70°C E* can be increased by increasing the amount of filler, decreasing the particle size, decreasing the total amount of plasticizer, and increasing the amounts of vulcanizing agent and vulcanization accelerator. Therefore, there is a tendency that the 70°C E* can be decreased by the reverse operation.
[0063] (Formula (3)) The relationship satisfied by equation (3) is as follows. (3) G / WL<0.0180
[0064] The tire of the present invention that satisfies the above formula (3) is a tire that has a relatively large maximum load capacity relative to the tire weight. The right side of formula (3) is preferably 0.0170, more preferably 0.0165, and even more preferably 0.0161. On the other hand, the lower limit of G / WL is not particularly limited from the viewpoint of the effects of the present invention, but is, for example, 0.0120.
[0065] The value of G / WL can be decreased by decreasing the value of G relative to the value of WL, and conversely, it can be increased by increasing the value of G relative to the value of WL.
[0066] As described above, WL is a value determined according to the tire section width Wt (mm), tire section height Ht (mm), and tire outer diameter Dt (mm). Fig. 1 or Fig. 2 illustrates the Wt, Ht, and Dt of a tire.
[0067] (Formula (4)) In the tire of the present invention, it is preferable that the 70° C. E* and the thickness T (mm) of the sidewall at the maximum width position of the tire satisfy the following relationship: (4) 70℃E*×T<31.5
[0068] The value of the right side of formula (4) is preferably 25.0, more preferably 20.0, even more preferably 16.0, even more preferably 15.0, even more preferably 14.0, even more preferably 13.0, even more preferably 12.0. There is no particular lower limit to the value of the left side of formula (4) from the viewpoint of the effects of the present invention, but it is, for example, 10.0.
[0069] The thickness T of the sidewall is the thickness of the rubber constituting the sidewall, measured along a normal line L of the tire maximum width position PW of the sidewall, as shown in Fig. 1. Here, the tire maximum width position PW is the position on the outer surface of the sidewall where the tire cross-sectional width Wt is measured.
[0070] The thickness T (mm) of the sidewall is not particularly limited as long as it is within the range of thickness that can be normally adopted. For example, in the case of a passenger car tire, T is preferably more than 1.0 mm, more preferably more than 1.5 mm, even more preferably more than 2.0 mm, and even more preferably 3.0 mm or more. On the other hand, T is preferably less than 10.0 mm, more preferably less than 9.5 mm, even more preferably less than 9.0 mm, even more preferably less than 8.5 mm, and even more preferably 8.0 mm or less.
[0071] (Micro-ridge forming part) The tire of the present invention preferably has a microridge-forming portion in which a plurality of microridges are formed on the outer surface of at least one of the pair of sidewalls.
[0072] In the microridge formation portion, the microridges may be in a single row in the radial direction of the tire, or in multiple rows. Here, "a single row in the radial direction of the tire" means that there are not two or more microridges lined up in the radial direction of the tire. Also, the microridges may be in a single row in the circumferential direction of the tire, or in multiple rows. Here, "a single row in the circumferential direction of the tire" means that there are not two or more microridges lined up in the circumferential direction of the tire. It is preferable that the microridges are provided in multiple rows in the radial direction of the tire and multiple rows in the circumferential direction of the tire.
[0073] The area of the micro-ridge formation is the area defined by a line encircling the outermost part of the multiple micro-ridges arranged at intervals of 0.50 mm or less when viewed from a direction perpendicular to the tire surface. The area of the micro-ridge formation is 10 mm 2 It is preferable that the micro-ridge forming portion is equal to or larger than the above because this can suppress stress concentration on the outer surface of the sidewall and contribute to improving the crack resistance of the sidewall. Furthermore, in the micro-ridge forming portion, the group of micro-ridges may be continuous or may be divided. Here, divided means that the spacing between the micro-ridges is greater than 1.0 mm. Therefore, it is sufficient that there is at least one micro-ridge forming portion on the outer surface of at least one of the pair of sidewalls, and there may be multiple micro-ridge forming portions.
[0074] (minor elevation) The shape of the micro-ridge is not particularly limited as long as it suppresses stress concentration on the outer surface of the sidewall and contributes to improving the crack resistance of the sidewall, and specifically includes a columnar shape, a frustum shape, a rib shape (striped shape), etc. Examples of the columnar shape include a cylindrical shape and a polygonal prism shape such as a triangular prism shape, a square prism shape, and a pentagonal prism shape. Examples of the frustum shape include a circular frustum shape and a polygonal prism shape such as a triangular frustum shape, a square frustum shape, and a pentagonal frustum shape. Examples of the rib shape include a cross-sectional shape perpendicular to the longitudinal direction of the rib-shaped micro-ridge, and any shape may be included. Examples of the cross-sectional shape include a rectangle or a trapezoid.
[0075] FIG. 3 shows a part of the microridge formation part in which a cylindrical microridge 2 is formed on the sidewall outer surface 1. FIG. 4 shows a part of the microridge formation part in which a square pyramidal microridge 3 is formed on the sidewall outer surface 1. FIG. 5 is a cross-sectional view taken along line XX in FIG. 4, and is a view of the microridges viewed from a direction perpendicular to a plane including a normal line to the sidewall outer surface. FIG. 5 shows the height h of the microridges 3, the maximum width w of the microridges 3, and the interval d of the microridges 3. FIG. 6 shows a part of the microridge formation part in which rib-shaped microridges 4 are formed on the sidewall outer surface 1. FIG. 7 is a cross-sectional view taken along line YY in FIG. 6, and is a view of the microridges viewed from a direction perpendicular to a plane including a normal line to the sidewall outer surface. FIG. 7 shows the height h of the microridges 4, the maximum width w of the microridges 4, and the interval d of the microridges 4.
[0076] Here, with respect to the microridges, "height" refers to the maximum height of the microridges measured along a normal line erected on the outer surface of the sidewall, "maximum width" refers to the maximum width of the microridges on the outer surface of the sidewall measured in one direction in which the microridges are arranged, and "spacing" refers to the minimum spacing of the microridges on the outer surface of the sidewall measured in one direction in which the microridges are arranged. Note that the height, maximum width, and spacing of the microridges are all measured with the outer surface of the sidewall developed on a plane.
[0077] The height of the micro-ridge at the maximum tire width position is preferably 0.03 mm or more, may be 0.05 mm or more, or may be 0.10 mm or more, while the height is preferably 0.50 mm or less, may be 0.45 mm or less, or may be 0.40 mm or less. The maximum width of the micro-ridge is preferably 0.03 mm or more, may be 0.05 mm or more, or may be 0.10 mm or more, while the maximum width is preferably 5.00 mm or less, may be 3.00 mm or less, may be 1.00 mm or less, or may be 0.50 mm or less. Furthermore, the spacing between the micro-ridges is preferably 1.00 mm or less, may be 0.70 mm or less, may be 0.50 mm or less, may be 0.30 mm or less, may be 0.10 mm or less, or may be 0.05 mm or less. The spacing between the micro-ridges may be at least half the maximum width, or may be the same as the maximum width. The density of the micro-ridges (pcs / cm 2 ) can be roughly calculated from the maximum width and interval of the micro-ridges. For example, in the case of the examples described later, it is about 700 pieces / cm 2 It is.
[0078] It is preferable that 20 or more micro-ridges are formed in at least one direction, because this can suppress stress concentration on the outer surface of the sidewall and contribute to improving the crack resistance of the sidewall.
[0079] It is preferable that the height of the micro-ridges gradually increases from the maximum tire width position toward the outer side in the tire radial direction, and also gradually increases from the maximum tire width position toward the inner side in the tire radial direction. This is because, although relatively large distortion occurs near the maximum tire width position of the sidewall, by making the height of the micro-ridges lower on the side closer to the maximum tire width position, it is believed that this reduces the non-uniformity of the rubber volume in the tire circumferential direction at the position where large distortion occurs, avoids stress concentration near the micro-ridges, and contributes to improving the crack resistance of the sidewall.
[0080] It is preferable that the micro-ridge has an arc-shaped recess on the outermost surface of the micro-ridge, like the micro-ridge 4 shown in Fig. 6. This is because such a configuration can prevent air from accumulating in the arc-shaped recess, thereby preventing poor appearance of the micro-ridge.
[0081] <Rubber composition> The rubber composition constituting the sidewall of the tire of the present invention will be described. The rubber composition contains a rubber component and a filler, and may further contain other compounding ingredients.
[0082] (Rubber component) The rubber component preferably contains at least one rubber component selected from the group consisting of isoprene-based rubber (IR-based rubber), styrene-butadiene rubber (SBR), and butadiene rubber (BR). The rubber component may contain at least two rubber components selected from the group consisting of IR-based rubber, SBR, and BR, or may contain IR-based rubber, SBR, and BR. Of these, the rubber component preferably contains IR-based rubber and BR. These rubber components may be extended rubbers extended with a plasticizer described below, or may be rubbers that have been modified or hydrogenated by adding hydrogen to double bonds.
[0083] <Isoprene rubber> Examples of isoprene-based rubber include natural rubber (NR), isoprene rubber (IR), modified NR, modified NR, modified IR, etc. As NR, for example, SIR20, RSS♯3, TSR20, etc., which are common in the tire industry, can be used. As IR, there is no particular limitation, and for example, IR2200, etc., which are common in the tire industry can be used. As modified NR, deproteinized natural rubber (DPNR), high-purity natural rubber (UPNR), etc., as modified NR, epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), grafted natural rubber, etc., as modified IR, epoxidized isoprene rubber, hydrogenated isoprene rubber, grafted isoprene rubber, etc. can be used. These may be used alone or in combination of two or more.
[0084] The content of the isoprene-based rubber in 100% by mass of the rubber component is preferably more than 20% by mass, more preferably more than 30% by mass, even more preferably more than 40% by mass, and even more preferably 45% by mass or more from the viewpoint of improving the breaking elongation and crack resistance of the rubber composition, while it is preferably less than 75% by mass, more preferably less than 65% by mass, and even more preferably less than 55% by mass from the viewpoint of suppressing deterioration due to heat, etc.
[0085] ≪SBR≫ There are no particular limitations on the SBR, and for example, emulsion-polymerized styrene-butadiene rubber (E-SBR), solution-polymerized styrene-butadiene rubber (S-SBR), etc. can be used. The SBR may be unmodified or modified. Hydrogenated styrene-butadiene copolymer (hydrogenated SBR) can also be used as the SBR. These may be used alone or in combination of two or more.
[0086] The styrene content of SBR is preferably more than 5.0 mass%, more preferably more than 7.5 mass%, and even more preferably 10.0 mass% or more. The styrene content is preferably less than 40.0 mass%, more preferably less than 35.0 mass%, and even more preferably less than 30.0 mass%. By keeping it within the above range, it is believed that micro styrene domains can be formed in the rubber component, making it easier to absorb strain due to deformation in the rubber composition. In this specification, the styrene content is defined as 1 It can be measured by H-NMR measurement.
[0087] The vinyl bond content of SBR is preferably more than 5 mol%, more preferably more than 10 mol%, and even more preferably more than 15 mol%. The vinyl bond content is preferably less than 65 mol%, more preferably less than 60 mol%, and even more preferably less than 50 mol%. The vinyl bond content can be measured by the above-mentioned method.
[0088] As the SBR, SBR extended with a plasticizer (extended SBR) can be used, or non-extended SBR can be used. When extended SBR is used, the amount of extension of SBR, i.e., the content of the extended plasticizer contained in SBR, is preferably 10 to 50 parts by mass per 100 parts by mass of the rubber solid content of SBR. Examples of the plasticizer used for extension include resins, oils, liquid polymers, and ester-based plasticizers, which will be described later.
[0089] As the SBR, for example, SBR manufactured and sold by Sumitomo Chemical Co., Ltd., JSR Corporation, Asahi Kasei Corporation, Nippon Zeon Co., Ltd., and the like can be used.
[0090] The content of SBR in 100% by mass of the rubber component may be 0% by mass, but may be, for example, more than 1% by mass, more than 5% by mass, or more than 10% by mass. The upper limit of the SBR content is preferably less than 40% by mass, more preferably less than 35% by mass, and further preferably 30% by mass or less.
[0091] The BR is not particularly limited, and examples of the BR that can be used include high cis BR with a high cis content, BR containing syndiotactic polybutadiene crystals, BR synthesized using a rare earth catalyst (rare earth BR), etc. These may be used alone or in combination of two or more.
[0092] In particular, the BR preferably contains high-cis BR having a cis content of more than 90% by mass. The cis content is more preferably more than 95% by mass, and more preferably 98% by mass or more. The cis content can be measured by the above-mentioned method.
[0093] The BR may be unmodified or modified. The modified BR may be modified BR having the same functional group as the modified diene rubber. The BR may be a hydrogenated butadiene polymer (hydrogenated BR).
[0094] As the BR, for example, products from Ube Industries, Ltd., JSR Corporation, Asahi Kasei Corporation, Zeon Corporation, etc. can be used.
[0095] From the viewpoints of fuel economy and crack growth resistance, the content of BR in 100% by mass of the rubber component is preferably more than 20% by mass, more preferably 25% by mass or more, even more preferably more than 30% by mass, even more preferably more than 35% by mass, even more preferably more than 40% by mass, even more preferably more than 45% by mass, even more preferably more than 50% by mass, and even more preferably 55% by mass or more. On the other hand, the upper limit is preferably less than 75% by mass, more preferably less than 70% by mass, and even more preferably less than 65% by mass.
[0096] <Other rubber components> As the rubber component, rubbers other than those mentioned above can be used. Examples of rubbers other than those mentioned above include diene rubbers such as styrene isoprene butadiene rubber (SIBR), chloroprene rubber (CR), and acrylonitrile butadiene rubber (NBR), and non-diene rubbers such as ethylene propylene diene rubber (EPDM), butyl rubber (IIR), and halogenated butyl rubber (X-IIR). These may be used alone or in combination of two or more.
[0097] The content of the diene rubber in 100% by mass of the rubber component is preferably more than 80% by mass, more preferably more than 90% by mass, and most preferably 100% by mass.
[0098] (Filler) The rubber composition of the present invention preferably contains at least one of silica and carbon black (CB). The carbon black preferably contains recovered carbon black (rCB).
[0099] <Silica> As the silica, dry process silica (anhydrous silica), wet process silica (hydrated silica), etc. can be used. Among them, wet process silica is preferred because it has a large number of silanol groups. As commercially available products, products from Degussa, Rhodia, Tosoh Silica Co., Ltd., Solvay Japan Co., Ltd., Tokuyama Corporation, etc. can be used. These may be used alone or in combination of two or more kinds. In addition to these silicas, silica made from biomass materials such as rice husks can also be used.
[0100] The nitrogen adsorption specific surface area of silica (N 2 SA) is preferably 50m 2 / g, more preferably 100m 2 / g, more preferably 150m 2 / g or more, more preferably 175m 2 / g or more. 2 The upper limit of SA is not particularly limited, but is preferably 600 m 2 / g, more preferably less than 350m 2 / g, more preferably less than 260m 2 By keeping it within the above range, the crack propagation resistance tends to be improved. 2 SA is the value measured by the above method.
[0101] From the viewpoint of reinforcing property, fuel efficiency, etc., the average primary particle size of silica is preferably less than 25 nm, more preferably less than 22 nm, even more preferably less than 20 nm, and even more preferably less than 18 nm. The lower limit of the average primary particle size is not particularly limited, but is preferably more than 3 nm, more preferably more than 5 nm, and even more preferably more than 10 nm. The average primary particle size of silica can be determined by the above-mentioned method.
[0102] The content of silica (total amount of silica) is preferably less than 30 parts by mass, more preferably less than 25 parts by mass, even more preferably less than 20 parts by mass, and even more preferably 15 parts by mass or less, based on 100 parts by mass of the rubber component. On the other hand, the content is preferably more than 1 part by mass, more preferably more than 3 parts by mass, even more preferably 5 parts by mass or more, and even more preferably 10 parts by mass or more. By being within the above range, it is believed that the rubber is adequately reinforced and the silica surfaces become more easily slippery against each other, improving the elongation at break (EB) and making it easier to improve the crack resistance.
[0103] <Silane coupling agent> When silica is used, a silane coupling agent may be used in combination, but in the present invention, it is preferable not to use a silane coupling agent even when silica is used. However, a silane coupling agent may be used within a range that does not affect the effects of the present invention. The silane coupling agent is not particularly limited, but examples thereof include sulfide-based silane coupling agents such as bis(3-triethoxysilylpropyl) disulfide and bis(3-triethoxysilylpropyl) tetrasulfide; mercapto-based silane coupling agents such as 3-mercaptopropyltrimethoxysilane, NXT-Z100, NXT-Z45, and NXT (3-octanoylthiopropyltriethoxysilane) manufactured by Momentive; vinyl-based silane coupling agents such as vinyltriethoxysilane and vinyltrimethoxysilane; 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-(2-aminopropyltriethoxy ... Examples of the silane coupling agents include amino-based silane coupling agents such as ethyl)aminopropyltriethoxysilane; glycidoxy-based silane coupling agents such as γ-glycidoxypropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane; nitro-based silane coupling agents such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; chloro-based silane coupling agents such as 3-chloropropyltrimethoxysilane and 3-chloropropyltriethoxysilane, etc., and sulfide-based silane coupling agents and / or mercapto-based silane coupling agents are preferred, and mercapto-based silane coupling agents are particularly preferred. These silane coupling agents may be used alone or in combination of two or more.
[0104] When containing silane coupling agent, the content (when using multiple silane coupling agents, the total amount) relative to 100 parts by mass of silica is preferably more than 1 part by mass, more preferably more than 3 parts by mass, and even more preferably more than 5 parts by mass, from the viewpoint of improving the dispersibility of silica.Furthermore, the content is preferably less than 20 parts by mass, more preferably less than 15 parts by mass, even more preferably less than 12 parts by mass, even more preferably less than 9 parts by mass, and even more preferably less than 7 parts by mass.
[0105] Carbon Black (CB) The carbon black is not particularly limited, and any carbon black that can be used in the tire industry can be used. Examples of such carbon black include N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, N660, and N762. Commercially available products include those from Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Co., Ltd., Lion Co., Ltd., Shin-Nichika Carbon Co., Ltd., and Columbia Carbon Co., Ltd. In addition, from the viewpoint of environmental load and from the viewpoint of reducing friction between the carbon black surface and rubber molecular chains and suppressing heat generation, recovered carbon black (rCB) obtained by pyrolysis of used tires may be used. These may be used alone or in combination of two or more.
[0106] Recovered carbon black can be obtained from the pyrolysis process of used pneumatic tires. For example, European Patent Application Publication No. 3427975, referring to "Rubber Chemistry and Technology", Vol. 85, No. 3, pp. 408-449 (2012), in particular pp. 438, 440, and 442, describes that recovered carbon black can be obtained by pyrolysis of organic materials at 550-800°C with the exclusion of oxygen, or by vacuum pyrolysis at relatively low temperatures (
[0027] ). Carbon black obtained from such pyrolysis processes usually lacks functional groups on its surface, as mentioned in
[0004] of Japanese Patent No. 6856781 (Comparison of Surface Morphology and Chemistry of Pyrolytic Carbon Black and Commercial Carbon Black, Powder Technology 160 (2005) 190-193).
[0107] The recovered carbon black preferably lacks functional groups on its surface, but may contain functional groups on its surface, or may be treated to contain functional groups on its surface, as long as the effect of the present invention is not affected. The treatment to contain functional groups on the surface of the recovered carbon black can be carried out by a conventional method. For example, in European Patent Application Publication No. 3173251, carbon black obtained from a pyrolysis process is treated with potassium permanganate under acidic conditions to obtain carbon black containing hydroxyl and / or carboxyl groups on its surface. In Japanese Patent No. 6856781, carbon black obtained from a pyrolysis process is treated with an amino acid compound containing at least one thiol group or disulfide group to obtain carbon black with an activated surface. The recovered carbon black according to the present embodiment also includes carbon blacks treated to contain functional groups on their surfaces.
[0108] As the recovered carbon black, commercially available products from Strable Green Carbon, LD Carbon, etc. can be used.
[0109] The average primary particle size of carbon black is preferably more than 20 nm, more preferably more than 25 nm, even more preferably more than 30 nm, and particularly preferably more than 35 nm. By setting the average primary particle size of carbon black within the above range, the rubber molecules bound by carbon black are minimized and become more flexible, so that it is considered that the polymer molecular chain can relax the stress against the input and suppress the occurrence of cracks. On the other hand, from the viewpoint of obtaining reinforcing properties, the average primary particle size is preferably less than 90 nm, more preferably less than 75 nm, and even more preferably less than 65 nm. The average primary particle size of carbon black is measured by the above-mentioned measurement method.
[0110] The nitrogen adsorption specific surface area of carbon black (N 2 SA) is 90m from the viewpoint of the effect of the present invention. 2 / g or less is preferable, and 80m2 / g is more preferable, and 70m 2 / g is more preferable, and 60m 2 More preferably, the N 2 SA is 10m 2 / g or more is preferable, and 20m 2 More preferably, 30m 2 More preferably, it is more than 35m 2 More preferably, it is more than 40m 2 More preferably, the N of carbon black is more than 1 / g. 2 The SA is measured by the above-mentioned measurement method.
[0111] When carbon black is contained, the content per 100 parts by mass of the rubber component is preferably more than 1 part by mass, more preferably more than 5 parts by mass, and even more preferably 10 parts by mass or more, from the viewpoint of obtaining reinforcement and preventing deterioration due to ultraviolet rays. Also, from the viewpoint of obtaining flexibility and relieving stress, the content is preferably less than 90 parts by mass, more preferably less than 70 parts by mass, even more preferably less than 60 parts by mass, even more preferably less than 50 parts by mass, and even more preferably 40 parts by mass or less.
[0112] ≪Formula (5)≫ When the rubber composition of the present invention contains silica and carbon black, when the content (parts by mass) of silica relative to 100 parts by mass of the rubber component is S and the content (parts by mass) of carbon black is C, it is preferable that S and C satisfy the following relationship. (5) S / C>0.50
[0113] The value of the right side of formula (5) is preferably 0.53, more preferably 0.55, even more preferably 0.57, and even more preferably 0.59. On the other hand, the value of the left side of formula (5) may be 1.00, 0.90, or 0.70.
[0114] ≪Formula (6)≫ When the rubber composition of the present invention contains silica and carbon black, and the carbon black contains recovered carbon black, it is preferable that S and rC satisfy the following relationship, where S is the content (parts by mass) of silica relative to 100 parts by mass of the rubber component, and rC is the content (parts by mass) of recovered carbon black. (6) S / rC>1.00
[0115] The value of the right side of formula (6) is preferably 1.10, more preferably 1.15, even more preferably 1.20, even more preferably 1.25, even more preferably 1.30, while the value of the left side of formula (6) may be 2.00, 1.80, or 1.50.
[0116] <Other filling materials> The rubber composition for tires of the present invention may contain other fillers in addition to silica and carbon black. Such other fillers are not particularly limited, and materials known in the rubber field can be used, such as inorganic fillers such as calcium carbonate, talc, alumina, clay, aluminum hydroxide, aluminum oxide, and mica.
[0117] <Filler content> From the viewpoint of the effects of the present invention, the content of the filler (total content of the fillers) is preferably more than 20 parts by mass, more preferably more than 30 parts by mass, and even more preferably 40 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit of the content is preferably less than 200 parts by mass, more preferably less than 150 parts by mass, even more preferably less than 100 parts by mass, and even more preferably less than 50 parts by mass.
[0118] (Other compounding agents) The rubber composition of the present invention may contain other compounding agents such as plasticizers, waxes, antioxidants, stearic acid, zinc oxide, vulcanizing agents, and vulcanization accelerators.
[0119] (Plasticizer) A plasticizer is a material that imparts plasticity to a rubber component, and is a concept that includes both plasticizers that are liquid (liquid state) at room temperature (25°C) and plasticizers that are solid at room temperature (25°C). Examples of plasticizers include resins, oils, liquid polymers, and ester-based plasticizers. The plasticizer content includes the amount of plasticizer in the rubber component extended by the plasticizer. For example, the oil content includes the amount of oil contained in oil-extended rubber. One type of plasticizer may be used alone, or two or more types may be used in combination.
[0120] <Resin> The rubber composition for tires of the present invention may contain a resin. Examples of the resin include petroleum resins, terpene resins, rosin resins, and phenol resins commonly used in the tire industry. These resin components may be used alone or in combination of two or more.
[0121] [Petroleum resin] Examples of the petroleum resin include C5 petroleum resin, aromatic petroleum resin, and C5C9 petroleum resin.
[0122] C5 petroleum resin refers to a resin obtained by polymerizing a C5 fraction, and may be a hydrogenated or modified resin. Examples of C5 fractions include petroleum fractions having 4 to 5 carbon atoms, such as cyclopentadiene, pentene, pentadiene, and isoprene. As a C5 petroleum resin, dicyclopentadiene resin (DCPD resin) is preferably used.
[0123] The aromatic petroleum resin refers to a resin obtained by polymerizing a C9 fraction, and may be a hydrogenated or modified resin. Examples of the C9 fraction include petroleum fractions having 8 to 10 carbon atoms, such as vinyltoluene, alkylstyrene, indene, and methylindene. Specific examples of aromatic petroleum resins that can be suitably used include coumarone-indene resins, coumarone resins, indene resins, and aromatic vinyl resins. As the aromatic vinyl resin, a homopolymer of α-methylstyrene or styrene or a copolymer of α-methylstyrene and styrene is preferred, and a copolymer of α-methylstyrene and styrene is more preferred, because they are economical, easy to process, and have excellent heat generation properties. As the aromatic vinyl resin, for example, commercially available products from Kraton, Eastman Chemical, etc. can be used.
[0124] The C5C9 petroleum resin refers to a resin obtained by copolymerizing the C5 fraction and the C9 fraction, and may be a hydrogenated or modified resin. Examples of the C5 fraction and the C9 fraction include the petroleum fractions mentioned above. As the C5C9 petroleum resin, for example, those commercially available from Tosoh Corporation, LUHUA, etc. can be used.
[0125] [Terpene resin] Examples of the terpene resin include polyterpene resins consisting of at least one selected from terpene compounds such as α-pinene, β-pinene, limonene, and dipentene; aromatic modified terpene resins made from the terpene compounds and aromatic compounds; terpene phenolic resins made from terpene compounds and phenolic compounds; and terpene resins obtained by subjecting these terpene resins to hydrogenation treatment (hydrogenated terpene resins). Examples of aromatic compounds that are raw materials for aromatic modified terpene resins include styrene, α-methylstyrene, vinyltoluene, and divinyltoluene. Examples of phenolic compounds that are raw materials for terpene phenolic resins include phenol, bisphenol A, cresol, and xylenol.
[0126] [Rosin-based resin] The rosin-based resin is not particularly limited, but examples thereof include natural rosin resin and rosin-modified resins obtained by modifying rosin by hydrogenation, disproportionation, dimerization, esterification, or the like.
[0127] [Phenol-based resin] The phenol-based resin is not particularly limited, but examples thereof include phenol formaldehyde resin, alkylphenol formaldehyde resin, alkylphenol acetylene resin, and oil-modified phenol formaldehyde resin.
[0128] [Resin content] The content of the resin component per 100 parts by mass of the rubber component is preferably more than 1 part by mass, more preferably more than 3 parts by mass, even more preferably more than 4 parts by mass, and even more preferably 5 parts by mass or more. The content of the resin component is preferably less than 30 parts by mass, more preferably less than 25 parts by mass, and even more preferably less than 20 parts by mass.
[0129] <Oil> Examples of the oil include process oil, vegetable oil, and animal oil. Examples of the process oil include paraffin-based process oil, naphthenic process oil, and aromatic process oil. In addition, a process oil having a low content of polycyclic aromatic compound (PCA) compounds can be used as an environmental measure. Examples of the low PCA content process oil include light extract solvate (MES), treated distillate aromatic extract (TDAE), and heavy naphthenic oil. In addition, from the viewpoint of life cycle assessment, waste oil after being used in rubber mixers and engines, or waste edible oil used in restaurants may be refined and used. The oil may be used alone or in combination of two or more types.
[0130] <Liquid polymer> The liquid polymer is not particularly limited as long as it is a polymer that is in a liquid state at room temperature (25° C.), and examples thereof include liquid butadiene rubber (liquid BR), liquid styrene butadiene rubber (liquid SBR), liquid isoprene rubber (liquid IR), liquid styrene isoprene rubber (liquid SIR), liquid farnesene rubber, etc. The liquid polymer may be used alone or in combination of two or more kinds.
[0131] <Ester-based plasticizers> Examples of ester-based plasticizers include dibutyl adipate (DBA), diisobutyl adipate (DIBA), dioctyl adipate (DOA), di-2-ethylhexyl azelate (DOZ), dibutyl sebacate (DBS), diisononyl adipate (DINA), diethyl phthalate (DEP), dioctyl phthalate (DOP), diundecyl phthalate (DUP), dibutyl phthalate (DBP), dioctyl sebacate (DOS), tributyl phosphate (TBP), trioctyl phosphate (TOP), triethyl phosphate (TEP), trimethyl phosphate (TMP), thymidine triphosphate (TTP), tricresyl phosphate (TCP), trixylenyl phosphate (TXP), etc. The ester-based plasticizers may be used alone or in combination of two or more.
[0132] <Content of plasticizers other than resin> When a plasticizer other than resin is contained, the content (total amount when a plurality of plasticizers are used) per 100 parts by mass of the rubber component is preferably more than 1 part by mass, more preferably more than 2 parts by mass, and even more preferably more than 3 parts by mass. The content of the plasticizer is preferably less than 50 parts by mass, more preferably less than 40 parts by mass, and even more preferably less than 30 parts by mass.
[0133] <Wax> The wax is not particularly limited, and any wax commonly used in the tire industry can be suitably used, such as petroleum wax, mineral wax, and synthetic wax. Of these, petroleum wax is preferred. Petroleum wax includes, for example, paraffin wax, microcrystalline wax, and selected special waxes thereof, and paraffin wax is preferred. Waxes that can be used include, for example, those manufactured and sold by Ouchi Shinko Chemical Industry Co., Ltd., Nippon Seiro Co., Ltd., Paramelt Co., Ltd., and the like. Waxes can be used alone or in combination of two or more kinds.
[0134] When the wax is contained, the content per 100 parts by mass of the rubber component is preferably more than 0.3 parts by mass, more preferably more than 0.5 parts by mass, and even more preferably 1.0 part by mass or more, while the content is preferably less than 4.0 parts by mass, more preferably less than 3.0 parts by mass, and even more preferably less than 2.0 parts by mass.
[0135] <Anti-aging agent> The antiaging agent is not particularly limited, and any of those commonly used in the tire industry can be suitably used. Examples of the antiaging agent include quinoline-based antiaging agents, quinone-based antiaging agents, phenol-based antiaging agents, phenylenediamine-based antiaging agents, and carbamic acid metal salts. Among them, phenylenediamine-based antiaging agents are preferred because they can more effectively improve the ozone resistance.
[0136] When an antioxidant is contained, the content per 100 parts by mass of the rubber component is preferably more than 0.5 parts by mass, more preferably more than 1.0 parts by mass, and even more preferably more than 2.0 parts by mass, while the content is preferably less than 7.0 parts by mass, more preferably less than 6.0 parts by mass, and even more preferably less than 5.0 parts by mass.
[0137] <Stearic acid> When stearic acid is contained, the content per 100 parts by mass of the rubber component is preferably more than 0.5 parts by mass, more preferably more than 0.7 parts by mass, and even more preferably more than 1.0 part by mass from the viewpoint of processability, while the content is preferably less than 10 parts by mass, more preferably less than 5 parts by mass, and even more preferably less than 3 parts by mass from the viewpoint of vulcanization rate.
[0138] <Zinc oxide> When zinc oxide is contained, the content per 100 parts by mass of the rubber component is preferably more than 0.5 parts by mass, more preferably more than 0.7 parts by mass, and even more preferably more than 1 part by mass from the viewpoint of processability, while the content is preferably less than 10 parts by mass, more preferably less than 7 parts by mass, and even more preferably less than 5 parts by mass from the viewpoint of abrasion resistance.
[0139] <Vulcanizing agent> The vulcanizing agent is not particularly limited, and known vulcanizing agents can be used, such as organic peroxides, sulfur-based vulcanizing agents, resin vulcanizing agents, and metal oxides such as magnesium oxide. Among these, sulfur-based vulcanizing agents are preferred. As the sulfur-based vulcanizing agent, for example, sulfur donors such as sulfur and morpholine disulfide can be used. Among these, sulfur is preferably used. The vulcanizing agent can be used alone or in combination of two or more.
[0140] Examples of sulfur include powdered sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur (oil-treated sulfur, special sulfur treated with a dispersant, master batch-type sulfur, etc.), and insoluble sulfur (oil-treated insoluble sulfur, etc.), and any of these can be used suitably. Among these, powdered sulfur and insoluble sulfur are preferred. Examples of sulfur that can be used include those manufactured and sold by Tsurumi Chemical Industry Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexis Co., Ltd., Nippon Kanzuri Kogyo Co., Ltd., Hosoi Chemical Industry Co., Ltd., etc.
[0141] When the vulcanizing agent is contained, the content relative to 100 parts by mass of the rubber component is preferably more than 0.4 parts by mass, more preferably more than 0.7 parts by mass, more preferably 1.0 parts by mass or more, and even more preferably more than 1.3 parts by mass. On the other hand, the content is preferably less than 6.0 parts by mass, more preferably less than 5.0 parts by mass, and even more preferably less than 3.0 parts by mass. When the content of the vulcanizing agent is within the above range, there is a tendency that an appropriate reinforcing effect is obtained, and the effect of the present invention tends to be better exhibited. In addition, when the vulcanizing agent contains a component other than sulfur, such as oil-treated sulfur, the content of the vulcanizing agent means the content of the sulfur component itself.
[0142] <Vulcanization accelerator> The vulcanization accelerator is not particularly limited, and known vulcanization accelerators can be used, such as sulfenamide-based, thiazole-based, thiuram-based, thiourea-based, guanidine-based, dithiocarbamic acid-based, aldehyde-amine-based or aldehyde-ammonia-based, imidazoline-based, or xanthate-based vulcanization accelerators. Among them, sulfenamide-based, thiuram-based, and guanidine-based are preferred, and sulfenamide-based are more preferred. As the vulcanization accelerator, for example, those manufactured and sold by Ouchi Shinko Chemical Industry Co., Ltd., Sanshin Chemical Industry Co., Ltd., etc. can be used. These vulcanization accelerators can be used alone or in combination of two or more.
[0143] Examples of sulfenamide vulcanization accelerators include N-tert-butyl-2-benzothiazolylsulfenamide (TBBS), N-cyclohexyl-2-benzothiazolylsulfenamide (CBS), and N,N'-dicyclohexyl-2-benzothiazolylsulfenamide (DZ). Examples of thiuram vulcanization accelerators include tetramethylthiuram monosulfide, tetramethylthiuram disulfide, and tetrabenzylthiuram disulfide (TBzTD). Examples of guanidine vulcanization accelerators include 1,3-diphenylguanidine (DPG), di-orthotolylguanidine, and orthotolylbiguanidine.
[0144] The content of the vulcanization accelerator relative to 100 parts by mass of the rubber component is preferably more than 0.3 parts by mass, more preferably more than 0.5 parts by mass, and even more preferably more than 0.6 parts by mass. On the other hand, the content is preferably less than 8.0 parts by mass, more preferably less than 5.0 parts by mass, and even more preferably less than 4.0 parts by mass. When the content of the vulcanization accelerator is within the above range, the breaking strength and elongation tend to be secured, and the effects of the present invention tend to be more favorably exhibited.
[0145] <Manufacturing> The rubber composition of the present invention can be produced by a known method, for example, by kneading the above-mentioned components using a rubber kneading device such as an open roll or an internal kneader (Banbury mixer, kneader, etc.).
[0146] The kneading step includes, for example, a base kneading step in which compounding ingredients and additives other than the vulcanizing agent and the vulcanization accelerator are kneaded, and a final kneading (F kneading) step in which the vulcanizing agent and the vulcanization accelerator are added to the kneaded product obtained in the base kneading step and kneaded. Furthermore, the base kneading step can be divided into a plurality of steps as desired.
[0147] The kneading conditions are not particularly limited, but examples include a method in which in the base kneading step, kneading is performed for 3 to 10 minutes at a discharge temperature of 150 to 170°C, and in the final kneading step, kneading is performed for 1 to 5 minutes at 70 to 110°C.
[0148] The tire of the present invention can be manufactured by a normal method using the above rubber composition. That is, an unvulcanized rubber composition obtained by blending the above components with the rubber component as necessary is extruded into the shape of a sidewall using an extruder equipped with a die of a predetermined shape, and the unvulcanized sidewall thus obtained is laminated together with a bead apex having a predetermined H and, if necessary, a bead reinforcing layer, together with other tire components on a tire building machine, and molded by a normal method to form an unvulcanized tire, and the unvulcanized tire is heated and pressurized in a vulcanizer to manufacture a tire. The vulcanization conditions are not particularly limited, and examples thereof include a method of vulcanizing at 150 to 200°C for 10 to 30 minutes.
[0149] <Application> Examples of the tire include pneumatic tires and non-pneumatic tires. Among them, pneumatic tires are preferred. The tire can be used as a passenger car tire, a large passenger car tire, a large SUV tire, a heavy load tire such as a truck or a bus tire, a light truck tire, a two-wheeled vehicle tire, a racing tire (high performance tire), etc. Among them, it can be preferably used as a passenger car tire. Here, a passenger car tire is a tire that is assumed to be mounted on a four-wheeled vehicle and has a maximum load capacity WL of 1400 kg or less. EXAMPLES
[0150] Examples (embodiments) that are considered to be preferable for carrying out the present invention are shown below, but the scope of the present invention is not limited to the examples. Tires obtained using the various chemicals shown below and according to each table were examined, and the results calculated based on the following evaluation method are shown in each table.
[0151] <Various chemicals> The chemicals used in the examples and comparative examples are summarized below.
[0152] IR rubber: Natural rubber (TSR20) BR: Ubepol BR150B manufactured by Ube Industries, Ltd. (cis content: 98% by mass, vinyl bond content: 1% by mass) SBR: HPR840 manufactured by ENEOS Materials Corporation (styrene content: 10.0% by mass, vinyl bond content: 42.0% by mole) CB (Carbon Black) 1: Show Black N550 (N) manufactured by Cabot Japan Co., Ltd. 2 SA:42m 2 / g, average primary particle diameter 48nm) CB (Carbon Black) 2: Show Black N660 (N) manufactured by Cabot Japan Co., Ltd. 2 SA:35m 2 / g, average primary particle size 80nm) rCB (recovered carbon black): Carbon black obtained from the pyrolysis process of tires (ash content: 17% by mass) Silica: Ultrasil VN3 (N) manufactured by Evonik Degussa 2 SA175m 2 / g, average primary particle diameter: 17nm) Wax: Ozoace wax made by Nippon Seiro Co., Ltd. Antioxidant 1: Nocrac 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Anti-aging agent 2: Nocrac RD (poly(2,2,4-trimethyl-1,2-dihydroquinoline)) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Oil: Diana Process NH-70S (aromatic process oil) manufactured by Idemitsu Kosan Co., Ltd. Zinc oxide: Zinc oxide No. 1 manufactured by Mitsui Mining & Smelting Co., Ltd. Stearic acid: Beads of stearic acid camellia manufactured by NOF Corporation Sulfur: SEIMI OT (insoluble sulfur containing 10% oil) manufactured by Nippon Kanretsu Kogyo Co., Ltd. Vulcanization accelerator: Noccela CZ (N-cyclohexyl-2-benzothiazolyl sulfenamide (CBS)) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.
[0153] <Production of Unvulcanized Rubber Composition> According to the compounding recipes shown in Tables 2-1 and 2-2 (collectively referred to simply as Table 2) and Tables 3-1 and 3-2 (collectively referred to simply as Table 3), chemicals other than sulfur and vulcanization accelerator are kneaded for 5 minutes using a 1.7 L closed Banbury mixer until the discharge temperature reaches 170°C, to obtain a kneaded product. Next, sulfur and vulcanization accelerator are added to the kneaded product obtained using a two-axis open roll, and the mixture is kneaded for 4 minutes until the temperature reaches 105°C, to obtain an unvulcanized rubber composition.
[0154] <Production of test tires> According to Tables 2 and 3, the obtained unvulcanized rubber composition is extruded into a sidewall shape using an extruder equipped with a nozzle of a specified shape, and the unvulcanized sidewall thus obtained is bonded together with other tire components on a tire building machine together with a bead apex having a specified H to form an unvulcanized tire, which is then press-vulcanized for 12 minutes under a condition of 170°C to produce each test tire (Tire 1: 265 / 70R18, Tire 2: 205 / 55R16).
[0155] Furthermore, the microbumps on the outer surface of the sidewall are formed during press vulcanization using a mold equipped with a side plate having an engraving for forming the microbump engraved on the surface facing the microbump forming portion. The shapes of the microbumps A and B are as follows. The height h (mm) is the height of the microbump at the maximum tire width position, the height h1 (mm) is the height of the microbump at the outermost position in the tire radial direction, and the height h2 (mm) is the height of the microbump at the innermost position in the tire radial direction. When the value of h1 is greater than h, the height of the microbump gradually increases from the maximum tire width position toward the outer side in the tire radial direction, and when the value of h2 is greater than h, the height of the microbump gradually increases from the maximum tire width position toward the inner side in the tire radial direction.
[0156] [Table 1]
[0157] <70℃ tanδ, 70℃ E*> A rubber test piece for viscoelasticity measurement, measuring 20 mm in length, 4 mm in width, and 1 mm in thickness, was cut from the inside of the sidewall of each test tire so that the long side was the tangent direction to the tire circumferential direction and the thickness was in the tire width direction. For each rubber test piece, the loss tangent (70°C tan δ) and complex modulus (70°C E*) (MPa) were measured in an extension deformation mode using a GABO Iplexer series under the following conditions: measurement temperature: 70°C, initial strain: 10%, dynamic strain: ±1%, frequency: 10 Hz.
[0158] <Crack resistance> The 265 / 70R18 test tire is mounted on a 18x8.5J rim, and the 205 / 55R16 test tire is mounted on a 16x6.5J rim. Each test tire is driven continuously for 40,000km using a drum (outer diameter: 1.7m) under the following conditions and a load is applied, and the total length of the cracks in the sidewall that have occurred after the drive is calculated. Load: 4.74kN Internal pressure: 290kPa Speed: 100km / h
[0159] Based on the total length of the cracks, the crack resistance index of the reference comparative example for each test tire is set to 100, and the crack resistance of each tire is expressed as an index using the following formula. The higher the index, the more excellent the crack resistance. (Crack resistance performance index) = (crack length of standard comparative example) / (crack length of each tire) × 100
[0160] [Table 2]
[0161] [Table 3]
[0162] [Table 4]
[0163] [Table 5]
[0164] <Embodiment> The following are preferred embodiments.
[0165] [1] A tire having a pair of sidewalls and a pair of bead apexes, A tire in which, when the loss tangent (tan δ) at 70°C of a rubber composition constituting the sidewall is 70°C tan δ, the complex modulus of elasticity (MPa) of the rubber composition at 70°C is 70°C E*, the height (mm) of the bead apex is H, the tire weight (kg) of the tire is G, and the maximum load capacity (kg) is WL, 70°C tan δ, 70°C E*, H, G, and WL satisfy the following relationships, and preferably the right side of formula (1) is 0.323, preferably the right side of formula (2) is 9.0, more preferably 8.0, and even more preferably 7.0, and preferably the right side of formula (3) is 0.0170. (1) 0.006×H-70℃ tan δ>0.320 (2) 70℃E*<10.0 (3) G / WL<0.0180 [2] The tire according to the above [1], wherein 70°C E* and T satisfy the following relationship, where T (mm) is the thickness of the sidewall at the maximum width position of the tire, and the right-hand side of formula (4) is preferably 25.0, more preferably 20.0. (4) 70℃E*×T<31.5 [3] The tire according to the above [1] or [2], wherein the right side of formula (1) is 0.328, preferably 0.329, more preferably 0.333, and even more preferably 0.339. [4] The tire according to any one of the items [1] to [3], wherein the right side of formula (2) is 6.0, more preferably 5.5, even more preferably 4.5, even more preferably 4.0, even more preferably 3.8, even more preferably 3.5, and even more preferably 3.0. [5] The tire according to any one of the above [1] to [4], wherein the right side of formula (3) is 0.0165, and more preferably 0.0161. [6] The tire according to any one of the above [2] to [5], wherein the right side of formula (4) is 16.0, more preferably 15.0, even more preferably 14.0, still more preferably 13.0, and still more preferably 12.0. [7] The tire according to any one of the above [1] to [6], wherein the rubber composition contains silica. [8] The tire according to any one of the above [1] to [7], wherein the rubber composition contains carbon black, and the carbon black contains recovered carbon black. [9] The rubber composition contains silica and carbon black, The tire according to any one of the items [1] to [6] above, wherein, when the content (parts by mass) of the silica is S and the content (parts by mass) of the carbon black is C relative to 100 parts by mass of the rubber component, S and C satisfy the following relationship, and the right side of formula (5) is preferably 0.53, more preferably 0.55, even more preferably 0.57, and still more preferably 0.59. (5) S / C>0.50
[10] The rubber composition includes silica and carbon black, and the carbon black includes recovered carbon black, The tire according to any one of the items [1] to [6] above, wherein, when a content (parts by mass) of the silica relative to 100 parts by mass of the rubber component is S and a content (parts by mass) of the recovered carbon black is rC, S and rC satisfy the following relationship, and the right side of formula (6) is preferably 1.10, more preferably 1.15, even more preferably 1.20, even more preferably 1.25, and even more preferably 1.30. (6) S / rC>1.00
[11] The tire according to any one of the above [1] to
[10] , wherein at least one of the pair of sidewalls has a microridge forming portion having a plurality of microridges formed on an outer surface thereof.
[12] The tire according to
[11] above, wherein the shape of the micro-protuberances is columnar, frustum or rib-like.
[13] The height of the micro-ridge is 0.03 mm or more and 0.50 mm or less, preferably 0.05 mm or more and 0.45 mm or less, more preferably 0.10 mm or more and 0.40 mm or less, and 20 or more are formed at intervals of 0.50 mm or less in at least one direction, and the micro-ridge forming portion is 10 mm 2 The tire according to
[11] or
[12] above, having an area of at least 100 mm.
[14] The tire according to any one of the items
[11] to
[13] above, wherein the maximum width of the microprotrusions is 0.03 mm or more and 5.0 mm or less, preferably 0.05 mm or more and 3.0 mm or less, and more preferably 0.10 mm or more and 1.0 mm or less.
[15] A tire according to any one of the items
[11] to
[14] , wherein the height of the micro-protrusions gradually increases from the maximum tire width position toward the outer side in the tire radial direction, and gradually increases from the maximum tire width position toward the inner side in the tire radial direction. [Explanation of symbols]
[0166] Wt Tire section width Ht Tire section height Dt Tire outer diameter H Bead apex height Cc Carcass Ba Bead Apex Bc bead core Br bead reinforcing layer T Sidewall Thickness PW Maximum tire width position L normal 1. Outer surface of sidewall 2 Micro-protuberance 3 Microscopic bumps 4 Microprotuberance w Maximum width of the micro-ridge d Spacing of micro-ridges h Height of the micro-ridge
Claims
1. A tire having a pair of sidewalls and a pair of bead apexes, A tire in which 70°C tan δ, 70°C E*, H, G, and WL satisfy the following relationship, where the loss tangent (tan δ) at 70°C of a rubber composition constituting the sidewall is 70°C tan δ, the complex modulus of elasticity (MPa) of the rubber composition at 70°C is 70°C E*, the height (mm) of the bead apex is H, the tire weight (kg) of the tire is G, and the maximum load capacity (kg) is WL. (1) 0.006×H-70℃tanδ>0.320 (2) 70℃E*<10.0 (3) G / WL<0.0180
2. 2. The tire according to claim 1, wherein 70° C. E* and T satisfy the following relationship, where T (mm) is a thickness of the sidewall at the maximum width position of the tire. (4) 70℃E**T<31.5
3. 2. The tire according to claim 1, wherein the right side of formula (1) is 0.
328.
4. The tire according to claim 1 , wherein the right side of formula (2) is 6.
0.
5. The tire according to claim 1 , wherein the right side of formula (3) is 0.0165.
6. The tire according to claim 2, wherein the right side of formula (4) is 16.
0.
7. The tire according to any one of claims 1 to 6, wherein the rubber composition contains silica.
8. The tire according to any one of claims 1 to 6, wherein the rubber composition contains carbon black, and the carbon black contains recovered carbon black.
9. The rubber composition includes silica and carbon black, The tire according to any one of claims 1 to 6, wherein a content (parts by mass) of the silica relative to 100 parts by mass of a rubber component is S and a content (parts by mass) of the carbon black is C, S and C satisfy the following relationship: (5) S / C>0.50
10. The rubber composition includes silica and carbon black, and the carbon black includes recovered carbon black. The tire according to any one of claims 1 to 6, wherein a content (parts by mass) of the silica relative to 100 parts by mass of a rubber component is S and a content (parts by mass) of the recovered carbon black is rC, S and rC satisfy the following relationship: (6) S / rC>1.00
11. 2. The tire according to claim 1, wherein at least one of the pair of sidewalls has a micro-ridge formation portion having a plurality of micro-ridges formed on an outer surface thereof.
12. The tire of claim 11, wherein the micro-ridges are pillar-like, frustum-like or rib-like in shape.
13. The micro-ridges have a height of 0.03 mm or more and 0.50 mm or less, and 20 or more are formed at intervals of 0.50 mm or less in at least one direction. The micro-ridge formation portion is 2 13. The tire according to claim 11 or 12, having an area of at least 10 mm.
14. The tire according to claim 11 or 12, wherein the maximum width of the micro-ridges is 0.03 mm or more and 5.0 mm or less.
15. 13. The tire according to claim 11 or 12, wherein the height of the micro-bumps gradually increases from the maximum tire width position toward the outside in the tire radial direction, and gradually increases from the maximum tire width position toward the inside in the tire radial direction.
Citation Information
Patent Citations
Rubber composition for tire member, cap tread and sidewall, and pneumatic tire
JP2021014506A